Activation of NLR-Mediated Autoimmunity in Arabidopsis Early in Short Days 4 Mutant - Xingchuan Huang; Xingchuan Huang; Yanan Liu; Jianhua Huang; Jianhua Huang; W. G. Dilantha Fernando; Xin Li; Xin Li; Shitou Xia (Frontiers in Plant Science, 2022)
From a reverse genetic screen using CRISPR/Cas9 gene editing tool, we unintentionally identified an autoimmune mutant. Map-based cloning and whole-genome sequencing revealed that it contains a deletion in SMALL UBIQUITIN-RELATED MODIFIER (SUMO) protease encoding gene EARLY IN SHORT DAYS 4 (ESD4). Previous studies reported that esd4 mutants accumulate elevated levels of plant defense hormone salicylic acid (SA). However, upregulated PATHOGENESIS-RELATED GENE 1 (PR1) expression in esd4 only partly relies on SA level. In this study, we show that plant metabolite N-hydroxypipecolic acid (NHP) biosynthetic genes are upregulated in esd4, and NHP biosynthesis mutant flavin-dependent-monooxygenase 1 (fmo1) partially suppresses the autoimmune phenotypes of esd4, suggestive of a requirement of NHP signaling for the autoimmunity in esd4. As activation of nucleotide-binding leucine-rich repeat immune receptors (NLRs) are associates with the biosynthesis of SA and NHP and lipase-like protein ENHANCED DISEASE SUSCEPTIBILITY 1 (EDS1) is a key component downstream of many NLRs, we examined the relationship between EDS1 and ESD4 by analyzing the eds1 esd4 double mutant. We found that eds1 largely suppresses esd4 autoimmunity and blocks the elevated expressions of SA and NHP biosynthesis-related genes in esd4. Overall, our study provides evidence supporting the hypothesis that SUMO protease ESD4 likely targets a yet to be identified guardee of NLR by removing its SUMO modification to avoid recognition by the cognate NLR. Loss of ESD4 results in activation of NLR-mediated autoimmunity.